2005
DOI: 10.1291/hypres.28.865
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Valsartan on the Progression of Chronic Renal Insufficiency in Patients with Nondiabetic Renal Diseases

Abstract: The present study tested the effects of valsartan, an angiotensin II receptor blocker, on the progression of renal insufficiency in patients with nondiabetic renal diseases. The study subjects were 22 patients with nondiabetic renal diseases whose serum creatinine (Cr) ranged from 1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 28 publications
0
9
0
1
Order By: Relevance
“…As well as the animal experiments, an ARB has been shown to reduce proteinuria and slow the progression of renal dysfunction in patients with nondiabetic renal disease. 30) The COMB group in this study was given SPRL and a low-dose of TELM which did not significantly lower the blood pressure. However, the renal dysfunction, proteinuria, glomerular injuries, and perivascular lesions were improved comparably to the high-dose TELM group in which the blood pressure was significantly lowered.…”
Section: Discussionmentioning
confidence: 82%
“…As well as the animal experiments, an ARB has been shown to reduce proteinuria and slow the progression of renal dysfunction in patients with nondiabetic renal disease. 30) The COMB group in this study was given SPRL and a low-dose of TELM which did not significantly lower the blood pressure. However, the renal dysfunction, proteinuria, glomerular injuries, and perivascular lesions were improved comparably to the high-dose TELM group in which the blood pressure was significantly lowered.…”
Section: Discussionmentioning
confidence: 82%
“…44) Multiple lines of clinical evidence have indicated that long-term inhibition of RAAS reduces proteinuria and attenuates the rate of deterioration of renal function in patients with diabetic and nondiabetic renal disease. [45][46][47][48] However, in SHR or patients with essential hypertension, detectable signs of renal injury do not occur until the later stage of life, 42) and it is not clear whether RAAS inhibitors can prevent or delay the onset of renal lesions in patients without pre-existing renal disease. In this respect, the present study demonstrated that lifelong antihypertensive therapy with an ARB can preserve renal function as indicated by creatinine clearance in SHR.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, African American Study of Kidney Disease and Hypertension (AASK) (27) suggested that ACE inhibitors slow renal disease progression in African American patients with hypertensive renal disease. Also as for the Asian population, we have reported that an ACE inhibitor and an ARB are effective in reducing proteinuria and slowing the deterioration of renal function in Japanese patients with chronic glomerulonephritis (28,29). Namely, an ACE inhibitor, benazepril, or an ARB, valsartan, inhibited the increase in serum creatinine and reduced proteinuria by 30-40% as compared with placebo ( Figure 7,8).…”
Section: Inhibitors Of Renin-angiotensin-aldosterone System In Antihymentioning
confidence: 89%